Attention as bounded resource and medium in cultural memory: A phenomenological or economic approach?. Issue 2 (8th December 2011) - BERNARDY, JÖRG
What is the role of attention in the dialectics of memory and communication? How far is attention functioning as a medium? Which role does attention play in the information management practices? Attention is not only fundamental to human existence but also to the process of understanding. If understanding is mediated by memory (tradition) and communication (dialogue) then attention can be identified with the medium. So whenever you search to explain the role and mechanisms of memory in the information society, the question of attention is asked immediately. Furthermore, attention can be analyzed under the following topics: as cognitive process, as subjective, intersubjective and cultural phenomenon, and as resource and medium within an 'Attention Economy'. Whereas the first aspect has to be seen in the context of empirical studies in psychology and cognitive sciences, the phenomenological, cultural, and economic aspects seem to have common points and similar implications in their theoretical approaches. In the last twenty years, the notion of attention has been the central core of several discourses in German phenomenology (Bernhard Waldenfels, 2004), economy (Franck) and cultural studies (Assmann). Similar to Georg Franck's theory of mental capitalism, the idea of an attention economy also was followed up in the American discourse (e.g. Goldhaber; Lanham). This article is supposed to explore the role of attention and its function as a medium within communication, cultural memory and science.